Problems of legislative provision of water use - Соколова, А. К. (Theory and practice of jurisprudence, 2016)
This article presents a comprehensive study of legal categories and the problems associated with providing the right water, analyzes specific occupational water use, concluded the need to improve environmental (water) law in the area of water rights.